Indigenous Community Perspectives on Forest Area Protection Governance Policy - Ahmad Dirwan; Mohammad Jamin; Jadmiko Anom Husodo (Lembaga Contrarius Indonesia, 2023)
The objective of this study is to objectively analyze and examine the legal protection of the community regarding the status of area land in West Lampung Regency. This research is sociolegal because it only determines law as a social phenomenon. This research was conducted in West Lampung Regency the research location was in Sukapura Village, Sumberjaya District, West Lampung Regency, and in the location of the forest land in the disputed area. The results of the authors can be concluded, firstly, that the regulation of tenure over forest area land in West Lampung Regency cannot provide legal protection for indigenous peoples because, in several findings, it is known that the land and the holder of rights over it are recorded for the first time in the registration book. Second, the regulation of valid land tenure rights in order to provide protection to the community regarding the status of forest area land in West Lampung is to check the status of the land. In the event that the means of proof as referred to in paragraph 1 are not available or are no longer available, proof of rights can be carried out based on the fact that the land parcel in question has physically been in possession for twenty years or more consecutively by the applicant for registration and preliminary introduction with conditions.